Faith, Fallibility, and the Virtue of Anxiety - Malone-France, D. author. aut Link
XI, 184 p.
Keywords: Malone-France brings together important themes from religious studies, philosophy, and political theory to articulate a fundamental re-conception of religious faith and an innovative argument for classic liberal norms.